ANALYSIS OF THE EFFECT F REVENUE SHARE OF MUDHARABAH AND MUSYARAKAH FINANCING PROCEEDS ON RETURN ON INVESTMENT (ROI) OF AN ISLAMIC BANK: A CASE STUDY - Azhar Alam; Maulidyah Indira Hasmarini; Novie Dwi Lestari; Afiq Miftahurizqi Alhaq (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
This study aimed to determine the effect of revenue sharing on the results of mudharabah and musyarakah financing on Return On Investment (ROI) at PT. Bukopin Sharia Bank 2011-2020. Islamic banks have two financing principles: profit sharing (mudharabah) and profit-sharing (musharaka). This study uses the Partial Adjustment Model (PAM) research method. The population in this study is Islamic banking which is included in the group of Islamic Commercial Banks. The sample used in this study is Bukopin Sharia Bank and is sourced from data from the Bukopin Sharia Bank's annual financial report data. The data used in this study uses secondary data, namely data obtained indirectly from the source in the form of data on the annual financial statements of Bank Syariah Bukopin taken from the official website www.syariahbukopin.co.id. From the research that has been done, the results show that the mudharabah and musyarakah financing variables have a positive effect on Return On Investment (ROI). Based on the results of this study, it is expected that Islamic banking will further increase mudharabah and musyarakah financing. These two products are the hallmarks of Islamic banks, namely profit sharing, because they can affect the rate of return on investment.